Teachers' Understanding and Attitudes to the Application of Deep Learning in the Independent Curriculum: A Case Study - Prawardhani, Neni Vila; Winarno, Winarno; Adi, Fadhil Purnama (Social, Humanities, and Educational Studies (SHES): Conference Series, 2026)
Deep learning is a learning approach that emphasizes meaningful understanding through mindful, meaningful, and joyful processes. This study aims to explore teachers' understanding and attitudes towards the application of deep learning in the Independent Curriculum in elementary schools. The qualitative research of this case study was carried out at SDN Pajaran 04, a favorite school with complete facilities where all teachers have participated in the Independent Curriculum training. The research subjects consisted of 8 teachers and 1 principal. Data were collected through in-depth interviews, observations, and documentation, then analyzed using the Miles and Huberman model. The results of the study show that: (1) teachers' understanding of the concept of deep learning still varies, with most teachers understanding deep learning as active learning but not fully understanding the essence of conscious learning; (2) teachers' attitudes are generally positive towards the application of deep learning, although there are concerns related to administrative burden and preparation time; (3) Factors supporting implementation include the support of the principal, the availability of facilities, and collaboration between teachers. This study concludes that a deep conceptual understanding and positive attitude of teachers are the key to the successful implementation of deep learning in the Independent Curriculum.